Anxiety relief in the post-pandemic era: a randomized trial on the integration of digital technology into dance art healing - Qiu, Suhui; Ruan, Chao; Wang, Ying (Frontiers in Psychology, 2025)
Trial designThis randomized controlled trial examined the effectiveness of digital technology-integrated dance therapy in alleviating anxiety symptoms associated with post-pandemic isolation.MethodsParticipants, including both professional and amateur dancers, were randomly assigned to either a traditional dance therapy group or a digital dance therapy group utilizing smart fitness mirrors. Anxiety levels were assessed using the Positive and Negative Affect Schedule (PANAS) before and after the intervention and a semi-structured interview was conducted. The trial spanned 3 months, with participants engaging in structured dance therapy sessions twice a week.ResultsThe findings revealed that digital dance therapy led to a significant improvement in overall anxiety reduction, as indicated by enhanced PANAS scores post-intervention. Participants in the digital dance group exhibited a notable increase in positive emotions, whereas reductions in negative emotions were less pronounced and, in some cases, even showed a slight increase. Approximately half of the participants experienced a significant decrease in anxiety symptoms, with the digital intervention demonstrating greater effectiveness compared to traditional dance therapy. Additionally, qualitative feedback indicated widespread acceptance of digital dance tools, with participants recognizing their potential in alleviating social and body image anxiety.ConclusionWhile digital dance therapy shows promise in enhancing positive emotions and reducing anxiety, its effectiveness in addressing negative emotions remains inconclusive. The study highlights the need for extended intervention periods, larger sample sizes, and further refinement of digital tools to optimize therapeutic outcomes. Future research should explore long-term efficacy and improve human-computer interaction in digital dance therapy.